If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 2) = 6(x + 6) + -5 Reorder the terms: -4(2 + x) = 6(x + 6) + -5 (2 * -4 + x * -4) = 6(x + 6) + -5 (-8 + -4x) = 6(x + 6) + -5 Reorder the terms: -8 + -4x = 6(6 + x) + -5 -8 + -4x = (6 * 6 + x * 6) + -5 -8 + -4x = (36 + 6x) + -5 Reorder the terms: -8 + -4x = 36 + -5 + 6x Combine like terms: 36 + -5 = 31 -8 + -4x = 31 + 6x Solving -8 + -4x = 31 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -8 + -4x + -6x = 31 + 6x + -6x Combine like terms: -4x + -6x = -10x -8 + -10x = 31 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 + -10x = 31 + 0 -8 + -10x = 31 Add '8' to each side of the equation. -8 + 8 + -10x = 31 + 8 Combine like terms: -8 + 8 = 0 0 + -10x = 31 + 8 -10x = 31 + 8 Combine like terms: 31 + 8 = 39 -10x = 39 Divide each side by '-10'. x = -3.9 Simplifying x = -3.9
| a/5=45/15 | | 2x-(5x+2)=12+5(x-1) | | 6b^2+24b-30=0 | | 3.5x-1=-1/2(-7x+2) | | 5y+20=3y-12 | | 18x-4-14x=2(2x-4)+4 | | 6(3x-1)-6=-4x+3(3x-8) | | 18x(-14x)= | | 3(3x-(6-5y+7x)+3y)= | | 2(4x-2)+5=7x-16 | | 294x-20+5=7x-16 | | ax+7=12 | | 9-7x=39-28x | | -5(x-2)=4(x+2)-7 | | 5x+3=46 | | 4y=3x+5y-2 | | 2x-(x-2)=8+6(x-1) | | 2x-3y=15 | | 4x-2=32x+5 | | 72-2x=3x+12 | | 2(7-3x)=6-x | | 12c+9=7c+14 | | 49a^2-16=0 | | 4(x-4)=6(2x+1) | | 26-18=2(x+7) | | y=2(4-x) | | x(2x-3)=x^2+10 | | 2(1+2w)+2w=80 | | 5(x-1)=9x-12 | | 8+9n-5=9n+8-5n | | 5x+3-4x=14-25 | | (3/6)y-6=-3 |